Countering Indeterminate Temporariness: Sheltering work in refugee camps - Kodeih, Farah; Schildt, Henri; Lawrence, Thomas B. (Organization studies, 2023)
The experience of temporariness is increasingly prevalent across the world, both for transient populations such as refugees and in work life characterized by precarious employment relationships. In this article, we examine how local institutional work can shape people’s experience of indeterminate temporariness and mitigate its pernicious effects. Our qualitative, inductive study is set in refugee camps in Lebanon, where indeterminate temporariness created an oppressive experience of time among Syrian refugees. We document the efforts of an NGO to help refugees rebuild meaningful lives by developing small-scale entrepreneurial ventures – efforts we conceptualize as ‘sheltering work’. Our analysis points to the potential for sheltering work to alleviate the oppressive effects of temporariness by bounding, containing, and structuring individuals’ day-to-day lives. Although sheltering work reshaped refugees’ experience of time, it did not eradicate the oppressive effects of indeterminate temporariness; instead, oppressive and reclaimed experiences of time coexisted, with individuals shifting between them. Our study theorizes sheltering work as a potent form of modest, local institutional work in the face of immutable institutions, and elaborates how individual experiences of time influence embedded agency.